Rebellion in Southern Rhodesia 1896-1897 - Chiotellis, Antonios (Mos Historicus: A Critical Review of European History, 2024)
The present study examines the rebellion of Ndebele and Shona against the rule of the British South Africa Company in 1896-97. The purpose of this study is to point out the nature, the causes, the development, and the results of the natives’ anti-colonial struggle. This was the first serious attempt to overthrow the British colonial rule in Sub-Saharan Africa. The study of this rebellion sheds light not only on the characteristics of the local societies but also on the nature of the British colonial engagement in Southern Rhodesia. A major concern of this study is to give prominence to the new situation caused by the British conquest and the grievances of Shona and Ndebele, which led to the rebellion. Last but not least, special focus will be given to the legitimizing colonial discourse, as an attempt to justify not only the British war conduct but also the British colonial expansion in Southern Rhodesia in general.